(untitled) (Sains Humanika, 2012)
Every teacher should have a variety of language teaching methods.Thus, this study attempted to determine the extent that the participants - teachers of the Iban language at secondary schools in Sarawak - applied the theory of Pedagogical Content Knowledge (PCK), which was introduced by Shulman. Specifically, this study aimed to (i) discover how far the teachers had instilled the PCK components in their teaching, and (ii) find out the challenges when implementing the PCK components. The study employed a qualitative method of case studies. Four teachers of the Iban language from the District Education Office in Subis were selected to be interviewed and observed. The research data in the form of interview transcripts were analyzed critically with the help of a software program, Nvivo8. The findings suggested that the PCK of the Iban teachers were influenced by their respective knowledge disciplines as their teaching options varied. It was also found that a good level of PCK resulted from the teachers’ passion and appreciation toward the Iban language. The manifestation of PCK in the teachers’ action was evident in six aspects of the teaching act, namely the comprehension, transformation, instruction, evaluation, reflection and new comprehension. The primary problems identified among the teachers were lack of references, limited knowledge about the teaching content, the value of the Iban language as a subject, infrastructure or facilities, attitude toward the language, and having to teach beyond the schedule. In sum, a good level of PCK can positively affect the teaching of the Iban language.